Factors Associated with Anterior Tibial Subluxation in Anterior Cruciate Ligament-Deficient Knees - Kakiage, Hibiki; Hatayama, Kazuhisa; Nonaka, Satoshi; Terauchi, Masanori; Iriuchishima, Takanori; Hashimoto, Shogo; Chikuda, Hirotaka (The Journal of Knee Surgery, 2025)
Anterior tibial subluxation (ATS) in knee extension is observed in knees with anterior cruciate ligament (ACL) injuries. Preoperative ATS adversely affects the postoperative anterior stability and increases the risk of early graft failure. To investigate the factors associated with preoperative ATS in knees with ACL injury. A total of 191 patients who underwent primary ACL reconstruction between 2017 and 2022 were included. Preoperatively, all patients underwent lateral radiography with full extension of both knees to evaluate the ATS. These 191 patients were divided into two groups based on ATS positivity. Positive ATS was defined as a side-to-side difference (SSD) in ATS > SD from the average SSD in ATS. The evaluation items included age, sex, height, weight, time from injury to surgery, mechanism of injury, posterior tibial slope, knee hyperextension angle, anterior tibial translation (ATT), meniscal tear on arthroscopy, and intraoperative pivot shift grade. There were 32 patients in the ATS-positive group. The overall average SSD in ATS was 1.7 ± 1.9 mm. Therefore, ATS > 3.6 mm was regarded as positive ATS. A logistic regression analysis indicated that positive ATS predictors were the ATT (odds ratio [OR]: 1.27; 95% confidence interval [CI]: 1.13–1.44; p < 0.001), >6 months from injury to surgery (OR: 2.89; 95% CI: 1.19–7.06; p = 0.02), and the contralateral hyper-extension angle (OR: 1.10; 95% CI: 1.00–1.21; p = 0.049). No significant difference was observed between the groups regarding meniscal tears. Anterior knee laxity, chronicity of ACL-deficiency, and hyperextension affect preoperative ATS in knees with ACL injuries. This study is a cross-sectional study providing level III evidence.
Keywords: anterior cruciate ligament; anterior tibial subluxation; anterior tibial translation